Examining the impact of early college experiences on the cumulative number of alcohol-related consequences. (September 2022) - Glenn, Shannon D.; Turrisi, Robert; Waldron, Katja A.; Mallett, Kimberly A.; Russell, Michael A.; Reavy, Racheal R.
Highlights: Students experienced an estimated total of 102 alcohol consequences across college. Willingness to experience consequences and drinking predicted total consequences. Parent approval of consequences indirectly predicted total consequences. Abstract: Objective: To estimate the total number of alcohol-related consequences students experience during 4 years of college and examine early college indicators that result in higher rates of consequences. Method: Undergraduate drinkers ( N  = 1, 744; 58% female; 87% White; 5% Hispanic) at a large northeastern university completed an online survey at the end of the fall and spring semesters during their first (T1, T2), second (T3, T4), third (T5, T6), and fourth (T7, T8) years of college (87% retention across the study). First, descriptive statistics were calculated to estimate the total number of alcohol-related consequences students experienced across all 4 years of college. Second, a structural equation model was examined to identify early college indicators that influence individuals experiencing more cumulative consequences. Results: Students experienced an average of 102 ( SD  = 89.91) alcohol-related consequences during 4 years of college. Next, early parental approval of consequences, but not peer drinking norms, were positively associated with students' willingness to experience consequences, which in turn, were positively associated with higher alcohol consumption and greater total consequences. Conclusions: Results estimated that, on average, students experienced 102 alcohol-related consequences across all 4 years of college. Parental approval of consequences influenced students' total consequences through their willingness to experience consequences and drinking behaviors. Findings from the current study have several important implications for interventions.